Analysis of the Energy Balance in the System Human – Clothing – Environment - Bartkevičius, S.; Račkienė, R.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2008)
In the system human – clothing – environment is researching correlation between these three factors. There is presented the energy balance equation in the human body, expressions of it components and analysis. There is analyzed influence of the environmental factors: ambient temperature, mean radiant temperature, air velocity and human wearing clothes insulation to the energy balance. Dependences on heat storage of some parameters are presented on the various environmental conditions and on the various activity level: sitting relaxed, walking on the rate 2 km/h, walking on the rate 5 km/h, running on the rate 7,5 km/h. These figures show how much heat storage needs to be eliminated from the body for the thermal comfort. At the same activity level is got dependence indicative of the variation rate of the human body temperature. Ill. 5, bibl. 6 (in English; summaries in English, Russian and Lithuanian).